Prosodic Proof of Syntactically Fixed Position - Peti-Stantić, Anita (2007)
The starting point for this paper is the limitations of comparative historical research on South Slavic clitics and the hypothetical nature of its conclusions, especially with respect to their prosodic status, which can be judged only on the basis of their position in the linear organization of the sentence. This paper deals with proclitic-enclitic syntagms of the type zà ; mene in Slovenian and Croatian and syntagms of the type záme (Slovenian) and zá me (Croatian). These syntagms are possible only because the short accusative pronominal forms were accented in the protolanguage. The author argues that these forms represent newly emerged clitics which preserved the feature of accentability in syntactically fixed positions in the western South Slavic languages, while this feature was lost in the eastern South Slavic languages.
ENG